1958
DOI: 10.1079/pns19580035
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress and Nutrition

Abstract: T h e following items, though not yielding calories, were included to increase interest in the fare: curry powder, Marmite, salt and pepper. Finally, tea and coffee were introduced as drinks, both in a soluble form which considerably simplifies preparation.This sledging ration is based on two previous Medical Research Council prototypes which have been used in the field. We have asked the users of our boxes to complete a full questionnaire and from their answers we will be guided as to further modifications. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, it has been shown that repeated exposure to hot or cold environments can lead to a form of physiological acclimatization (Fox, 1958; Leppaluoto and Hassi, 1991; Jansky et al., 1996; Lee et al., 2010). It may be that it is easier for the occupants of NV buildings, who are normally exposed to non‐neutral environments with varied thermal stimulation, to become physiologically acclimated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that repeated exposure to hot or cold environments can lead to a form of physiological acclimatization (Fox, 1958; Leppaluoto and Hassi, 1991; Jansky et al., 1996; Lee et al., 2010). It may be that it is easier for the occupants of NV buildings, who are normally exposed to non‐neutral environments with varied thermal stimulation, to become physiologically acclimated.…”
Section: Introductionmentioning
confidence: 99%